The Creative Process in the Creation of Tabuh Lelambatan Kreasi Works by I Ketut Gede Asnawa - Manik, I Made Dwi Rustika; Yudarta, I Gede; Ardini, Ni Wayan (Institut Seni Indonesia Bali, 2025)
Traditional music is experiencing rapid development from various aspects, including the creative process of making original works and the psychological expression of the artist in the creation process. This research examines the creative process in working on lelambatan music by I Ketut Gede Asnawa, with the aim of analyzing the stages of creation and exploring the knowledge contained in the work. The method used is qualitative with an ethnomusicology approach, which emphasizes direct involvement in the cultural context. The research location was determined purposively, while data collection techniques included observation, interviews, and in-depth documentation. The results showed that the creativity process includes three main modalities: imagination, skill, and sensitivity. In addition, “The Four P's of Creativity” approach (person, process, press, and product) plays an important role in the dynamics of creation. The resulting works are widely appreciated for demonstrating artistic integrity, depth of process, and high sincerity in realizing monumental works of art.